2012
DOI: 10.1371/journal.pone.0052123
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of MicroRNAs Associated with Myogenesis by Deep Sequencing of Serial Developmental Skeletal Muscles in Pigs

Abstract: MicroRNAs (miRNAs) are short, single-stranded non-coding RNAs that repress their target genes by binding their 3′ UTRs. These RNAs play critical roles in myogenesis. To gain knowledge about miRNAs involved in the regulation of myogenesis, porcine longissimus muscles were collected from 18 developmental stages (33-, 40-, 45-, 50-, 55-, 60-, 65-, 70-, 75-, 80-, 85-, 90-, 95-, 100- and 105-day post-gestation fetuses, 0 and 10-day postnatal piglets and adult pigs) to identify miRNAs using Solexa sequencing technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 53 publications
6
58
2
Order By: Relevance
“…The associated in vivo changes in vascular development, neuromuscular maturation, as well as complex modulation of the extracellular matrix during this rapid growth and maturation of skeletal muscle tissue, also needs to be considered. Greater insight into interactions between the many forms of RNAs and proteins that regulate muscle growth and maintain homeostasis, is of central importance to livestock industries related to improvement of meat quality and production using molecular approaches (Hou et al, 2012;Li et al, 2012) and to clinical muscle disorders. For example, many ncRNAs have been identified in cases of aberrant muscle growth and muscle atrophy, including genetic diseases as Duchenne muscular dystrophy (Neguembor et al, 2014;Twayana et al, 2013), inflammatory conditions like cachexia (Soares et al, 2014) and age-related muscle wasting (Drummond et al, 2011); therapeutic modulation of many ncRNAs by exercise has recently been demonstrated (Zacharewicz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The associated in vivo changes in vascular development, neuromuscular maturation, as well as complex modulation of the extracellular matrix during this rapid growth and maturation of skeletal muscle tissue, also needs to be considered. Greater insight into interactions between the many forms of RNAs and proteins that regulate muscle growth and maintain homeostasis, is of central importance to livestock industries related to improvement of meat quality and production using molecular approaches (Hou et al, 2012;Li et al, 2012) and to clinical muscle disorders. For example, many ncRNAs have been identified in cases of aberrant muscle growth and muscle atrophy, including genetic diseases as Duchenne muscular dystrophy (Neguembor et al, 2014;Twayana et al, 2013), inflammatory conditions like cachexia (Soares et al, 2014) and age-related muscle wasting (Drummond et al, 2011); therapeutic modulation of many ncRNAs by exercise has recently been demonstrated (Zacharewicz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gli2 expression can also be decreased by oxidative stress in both animal models and in cultured astrocytes (Xia et al , 2012; Ji et al , 2012). Studies have shown that microRNAs participate in development and cell differentiation through regulating growth related gene expression (Kim, 2005; Hou et al , 2012; Kawahara et al , 2012). Moreover, a recent study shows that miR-326 represses Shh signaling activity by directly targeting Gli2 expression in embryonic lung epithelium cells (Jiang et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation and differentiation are mutually exclusive during muscle regeneration, and miRNAs are critically involved in balancing these two processes [43]. Many miRNAs, such as miR-1, miR-133, miR-29, miR-214, miR-206, miR-486, miR-208b, and miR-499 were involved in the regulation of skeletal myogenesis by binding to its target genes [44, 45]. For example, in mice, miR-1 and miR-133 are clustered on the same chromosomal loci and transcribed together in a tissue-specific manner during development, but miR-133 enhances proliferation by repressing serum response factor, whereas miR-1 promotes myogenesis through repressing histone deacetylase 4 [17].…”
Section: Discussionmentioning
confidence: 99%